Balancing Act: Insights into Burnout and Work-life Dynamics among Experience Educators in private Institutions - Ishak, Nisrin; Abdul Manan, Dewi Izzwi; Hamzah, Fatimah Bibi; Ayop, Syafiq; A. Gani, Norhaninah (2024)
This qualitative study explores burnout among higher educators in private institutions through evidence from semi-structured interviews. Twenty-one respondents, all with over five years of tenure, were selected for in-depth interviews. The study examines the impact of burnout on educators' work-life balance and how they articulate their experiences, particularly the strategies they employ to voice concerns about their well-being. By analyzing the interplay between professional exhaustion and personal life, this research contributes to a deeper understanding of both structural and individual factors that influence burnout in the private education sector. The findings aim to inform policies and practices, offering pathways for higher education institutions to create environments that mitigate burnout and promote a healthier work-life balance